Pengaruh Penerapan Sistem Absensi Fingerprint Dan Kompensasi Terhadap Tingkat Efektivitas Kinerja Di Kantor Bina Mandiri Syariah Bekasi - Yolanda Agustina Pardede; Indah Wahyu Maesarini (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine the effect of the application of fingerprint attendance and compensation on the level of effectiveness of the performance of employees of the Bina Mandiri Syariah Cooperative in bekasi city. The population in this study was all employees at the Bina Mandiri Syariah office in Bekasi City. using total sampling technique, all 27 employees were used as research respondents. The analysis technique used is multiple regression analysis with t-test and F test. Based on the results of the study, the regression equation was obtained as follows: Y' = 10.027 + 0.395 X1 + 0.399 X2+ e. This regression equation shows that performance is affected by the use of fingerprint attendance and compensation. The results of another study concluded that the use of fingerprint attendance and compensation had a positive and significant influence on employee performance at the Bekasi Bina Mandiri Syariah Office so that all research hypotheses were accepted.